Job satisfaction, burnout, and safety behavior in air traffic controllers: a mediation analysis and decision tree insights - Li, Xiuyi; Huang, Zhuocheng; Peng, Xing; Zhang, Junjie; Liu, Yueying; Luo, Yuchuan; Guo, Lingfeng (Frontiers in Public Health, 2025)
IntroductionThis study aims to explore the mediating role of burnout in the relationship between job satisfaction and safety behavior among air traffic controllers (ATCs), and to identify the most influential factor affecting ATCs’ safety behavior using a decision tree model.MethodsData were collected from 357 ATCs using established questionnaires measuring job satisfaction, burnout, and safety behavior. Bootstrap analysis was employed to examine the mediating effect of burnout, and a decision tree model was applied to determine the key factors influencing safety behavior.ResultsThe bootstrap analysis revealed that burnout partially mediated the relationship between job satisfaction and safety behavior, accounting for 40% of the total effect. The decision tree model identified burnout as the primary predictor of safety behavior, followed by job satisfaction and other factors.DiscussionThese findings underscore the critical role of burnout in influencing ATCs’ safety performance. Enhancing safety behavior should prioritize targeted interventions to reduce burnout, in addition to addressing job satisfaction and other contributing factors.